Natural convection in a differentially heated cavity using splitting method - Ubaidullah, S. (2013)
The solution of thermally-driven flow of Navier-Sto kes equation, in Boussinesq approximation, is presented. The results are obtain ed using splitting method and in good agreement with available benchmark numerical solutions. The c onvection terms are explicitly integrated using 3-step Range-Kutta scheme. Buoyancy-driven fluid fl ows data in a differentially heated cavity for low Rayleigh numbers (R=10 3 , R=10 4 and R=10 5 ) are presented.